ANALIZING ISNAD-CUM-MATN OF TAUḤID PHRASE ON PROPHET’S FLAG HADITH - Amir, Abdul Muiz; Akbar, Akbar; Ainurrofiq, Faiq; Sempo, Muhammad Widus (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2021)
The flag inscribed with the phrase tauḥīd has been claimed by Jihadist-extremism groups to use the narrative hadith as a representation of the flag of the Prophet Muhammad (Liwā’ and Rāyah). This phenomenon inspires researchers to carry out in-depth investigations on the history of the hadith, either through micro analysis (isnād) or macro analysis (matn). The purpose of this investigation is to reveal the status and motive for the existence of the phrase tauḥīd on the Prophet’s flag. This research uses a qualitative interpretive study to explore the historical-critical paradigm through isnād-cum-matn approach by Harald Motzki. The findings show that the phrase tauḥīd, which is claimed to be part of the symbol of the Prophet’s flag, is only the form of insertion (idrāj) by Ḥayyan bin Ubaidillah as “the real common link”. The deviation was carried out as propaganda against the political contestation between the Abbasiyya dynasty and the Umayya dynasty in Egypt. This study’s results supply a new perspective that the religious symbols used as religious identity are not all based on valid sources. Keywords: Prophet’s Flag, Tauḥīd Phrase, Hadith, Isnād-cum-Matn, Political Religion Symbolic